2014
DOI: 10.1177/0363546514553181
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play and Recurrent Instability After In-Season Anterior Shoulder Instability

Abstract: In the largest prospective study evaluating shoulder instability in in-season contact athletes, 27% of athletes returned to play and completed the season without subsequent instability. While the majority of athletes who return to sport complete the season, recurrent instability events are common regardless of whether the initial injury was a subluxation or dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
122
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 49 publications
4
122
0
1
Order By: Relevance
“…1 Nonoperative management of glenohumeral instability has been associated with high rates of recurrence in multiples studies, with recurrence rates ranging from 37% to 85%. [2][3][4][5][6][7][8][9] Arthroscopic stabilization procedures have been similarly associated with recurrent instability, with recurrence rates ranging from 10.8% to 21.1%. [10][11][12][13] As a result, it has become essential for physicians to recognize clinical factors that place patients at increased risk of failed nonoperative or arthroscopic treatment.…”
mentioning
confidence: 99%
“…1 Nonoperative management of glenohumeral instability has been associated with high rates of recurrence in multiples studies, with recurrence rates ranging from 37% to 85%. [2][3][4][5][6][7][8][9] Arthroscopic stabilization procedures have been similarly associated with recurrent instability, with recurrence rates ranging from 10.8% to 21.1%. [10][11][12][13] As a result, it has become essential for physicians to recognize clinical factors that place patients at increased risk of failed nonoperative or arthroscopic treatment.…”
mentioning
confidence: 99%
“…Symptoms of shoulder instability have the potential to not only influence a person's athletic participation but also affect quality of life and function in everyday activities. 4,8 Shoulder stabilization surgery, whether open or arthroscopic, has proven to be an effective intervention to prevent recurrence while allowing athletes to return to sport. 21 Studies have reported wide-ranging return to play rates between 48% to 100% despite good scores on functional outcome measures such as the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), American Shoulder and Elbow Surgeons (ASES), and L'Insalata scores.…”
mentioning
confidence: 99%
“…Only 12 athletes (27%) completed the season without recurrence. Athletes with a subluxation were 5.3 times more likely to return to sport during the season than those with a dislocation [74]. They found the majority of athletes returned to sport in 10 days.…”
Section: In-season Athletesmentioning
confidence: 98%
“…This typically entails a brief period of immobilization (3-10 days) followed by a progressive physical therapy protocol that focuses on cryotherapy, restoration of normal range of motion, rotator cuff and periscapular strengthening, stabilization drills, and finally, sport-specific drills over a 2-3-week period [71][72][73]. Dickens et al demonstrated that a period of immobilization is not necessary, and an accelerated rehabilitation program can be beneficial in a percentage of intercollegiate athletes with inseason anterior shoulder instability [74]. With progressive physical therapy and occasional adjunctive use of shoulder stabilization bracing, the authors found that 33 of 45 (73%) patients were able to return to sport for either all or part of the season, with a median of only 5 days lost from competition.…”
Section: Physical Therapymentioning
confidence: 99%